Modeling and Stability Analysis of an Eco-epidemiological Model - Naji, Raid; Yaseen, Rasha (Iraqi Journal of Science, 2024)
In this paper,a prey-predator model with infectious disease in predator populationis proposed and studied. Nonlinear incidence rate is used to describe the transition ofdisease. The existence, uniqueness and boundedness of the solution are discussed.The existences and the stability analysis of all possible equilibrium points arestudied. Numerical simulation is carried out to investigate the global dynamicalbehavior of the system.